PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMP ISLAM AS-SHOFA PEKANBARU - Rahmi Fauziah; Sehatta Saragih; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was motivated by the result of learning mathematics of VII.3 students of SMP Islam As-Shofa Pekanbaru which is still under the KKM with percentage 52.00% on subject matter of algebraic forms. This research aims to improve the learning process and improve student learning achievement by applying cooperative learning model with structural NHT approach. This type of research is a classroom action research with two cycles. The subject of this research is the students of class VII.3 of SMP Islam As-Shofa Pekanbaru second semester of academic year 2017/2018 which amounted to 25 students with heterogeneous academic level. The data was collected by doing observation of teachers and students activities and formative test. The results showed that there was a better improvement in the learning process from cycle I to cycle II. This is seen in students who have participated actively and work together in the learning process. In addition, the number of students who achieved KKM on the basic score, formative test I (first cycle), formative test II (second cycle) were 52.00%, 56.00%, and 72.00%, respectively. The percentage of achievement of this KKM also shows improvement from before action to after action so that it can be said that student learning achievement also increase. The results of this research indicate that cooperative learning model with structural NHT approach can improve the learning process and improve the learning achievement of mathematics students VII.3 SMP Islam As-Shofa Pekanbaru second semester of the academic year 2017/2018.Key Words: Math Learning Achievement, Cooperative Learning Model With Structural Numbered Heads Together (NHT) Approach.